2020
DOI: 10.4018/ijkm.2020070101
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Knowledge Adoption and Cognitive Learning in the Knowledge Transfer Process

Abstract: This study aims to investigate the influence of knowledge adoption (intention to adopt knowledge) and cognitive learning in the knowledge transfer process. The moderating impact of cognitive learning strategy is also explored. Building on cognitive learning theories, a model was developed to examine the knowledge recipient's intention to adopt knowledge and his/her cognitive learning. As this study follows quantitative approach, the model was tested empirically using a survey of 615 white-collar workers in Tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…In another study by Rhodes et al (2008b) revealed that personalized (tacit) knowledge transfer had a strong influence on innovative capabilities development and process innovation had a greater impact on organizational performance than product innovation. Srisamran and Ractham (2020) revealed that intention to receive knowledge can enhance the aptitude of white-collar workers in Thailand. This finding emphasizes the need for management of organizations to understand the knowledge recipient of their employees before engaging in knowledge transfer.…”
Section: Related Empirical Reviewsmentioning
confidence: 99%
“…In another study by Rhodes et al (2008b) revealed that personalized (tacit) knowledge transfer had a strong influence on innovative capabilities development and process innovation had a greater impact on organizational performance than product innovation. Srisamran and Ractham (2020) revealed that intention to receive knowledge can enhance the aptitude of white-collar workers in Thailand. This finding emphasizes the need for management of organizations to understand the knowledge recipient of their employees before engaging in knowledge transfer.…”
Section: Related Empirical Reviewsmentioning
confidence: 99%
“…Moreover, Sussman and Siegal (2003) in their study highlighted that effective sharing of knowledge is only possible when knowledge shared is being learned by the recipient of knowledge. This narrow downs the importance of individual learning in a knowledge sharing process (Srisamran & Ractham, 2020). The review of literature has made it evident that knowledge sharing behaviour has been studied on a vast scale by the researchers considering various aspects.…”
Section: Knowledge Sharing Behaviour Conceptmentioning
confidence: 99%
“…Any form of representation of practical information is knowledge, which will actively help an individual to perform tasks and manage related cognitive and analytical processes [10]. Quality knowledge is always composed of a complex combination of data, skills, information, expert opinions and empirical experience.…”
Section: Data Information Knowledgementioning
confidence: 99%